The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.4310/mrl.1997.v4.n4.a11
|View full text |Cite
|
Sign up to set email alerts
|

Positivity conditions for bihomogeneous polynomials

Abstract: IntroductionIn this paper we continue our study of a complex variables version of Hilbert's seventeenth problem by generalizing some of the results from [CD]. Given a bihomogeneous polynomial f of several complex variables that is positive away from the origin, we proved that there is an integer d so that ||z|| 2d f (z, z) is the squared norm of a holomorphic mapping. Thus, although f may not itself be a squared norm, it must be the quotient of squared norms of holomorphic homogeneous polynomial mappings. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 6 publications
0
37
0
Order By: Relevance
“…For example, compactness of N q implies global regularity in the sense of preservation of Sobolev spaces [32]. Also, the Fredholm theory of Toeplitz operators is an immediate consequence of compactness in the ∂-Neumann problem [6,27,50]. There are additional ramifications for certain C * -algebras naturally associated to a domain in C n [41].…”
Section: Background For Bounded Pseudoconvex Domainsmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, compactness of N q implies global regularity in the sense of preservation of Sobolev spaces [32]. Also, the Fredholm theory of Toeplitz operators is an immediate consequence of compactness in the ∂-Neumann problem [6,27,50]. There are additional ramifications for certain C * -algebras naturally associated to a domain in C n [41].…”
Section: Background For Bounded Pseudoconvex Domainsmentioning
confidence: 96%
“…In [6] it is shown that compactness of the ∂-Neumann operator implies compactness of the commutator [P , M], where P is the Bergman projection and M is pseudodifferential operator of order 0. In [17] it is shown that compactness of the canonical solution operator to ∂ restricted to (0, 1)-forms with holomorphic coefficients implies compactness of the commutator [P , M] defined on the whole L 2 (Ω).…”
Section: Background For Bounded Pseudoconvex Domainsmentioning
confidence: 99%
“…When deciding nonnegativity of polynomials using traditional methods, complexities of algorithms increase rapidly as variable numbers and degrees of the polynomials increase [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…, c r n2 (except all zeros) have same signs in the σ coordinate system. Analogously, by finite steps of SDS, (8) …”
mentioning
confidence: 99%
“…Consequently with these formulas boundedness and compactness of N and S are equivalent. For compactness see [1].…”
Section: Preliminariesmentioning
confidence: 99%